0168 Effects of School Night Sleep Duration and Circadian Preference on Student Tardiness: An Investigation in a Middle-School Aged Sample. (27th May 2020) - Tran, K M; Cook, J D; Blair, E E; Peppard, P E; Plante, D T
Abstract: Introduction: Sleep and circadian factors play an important role in school attendance, academic performance, and daytime behaviors among adolescents. This investigation assessed school night sleep duration (SNSD) and circadian preference (CP) association with first period tardies (FPT) using a middle-aged sample from the Madison (Wisconsin) Metropolitan School District (MMSD), prior to implementation of a planned district-wide delay in middle school start times. Methods: 4, 175 middle-school aged students from 12 MMSD schools completed a sleep survey, which included SNSD and a validated 4-level measure of CP. Self-reported SNSD between 4-and-12 hours served as final sample inclusion criterion. Mixed effects modeling was employed with students nested within school. Linear regression determined SNSD and CP effect on student tardiness. Individual, year-long FPT served as outcome variable. Inclusion of SNSD quadratic term was not statistically indicated. Full model covariates included age, sex, race, parent educational level, homelessness, free and reduced lunch, and special education status. Results: Final sample included 3, 860 students. Univariate regression determined a significant CP association with FPT [β=1.20, 95% CI (0.54, 1.86), F(1, 10.41)=13.7, p=0.004), but not SNSD [β=-0.31, 95% CI (-0.70, -0.09), F(1, 10.21)=2.5, p=0.14]. SNSD and CP interaction was not significant. CP significance was maintained in the full model [β=1.24, 95% CI (-0.70, -0.09), F(1, 11.21)=13.7, p=0.004]. Evening preference associated with 3.72 more FPT, relative to morning preference. Conclusion: Results suggest evening preference is associated with increased risk of tardiness among middle school students. Future research that examines the relationships between delayed school start times, circadian preference, and impact on school tardiness is indicated. Support: This research was generously supported by a grant from the Madison Education Partnership (MEP).